PENGEMBANGAN EDU-AGROWISATA MELALUI PEMBERDAYAAN PEREMPUAN PADA KWT AZALEA FARM DENGAN PENDEKATAN ABCD (ASSET BASED COMMUNITY DEVELOPMENT) - Pratiwi, Yunita Niqrisah Dwi; Setiawati, Donna; Wulandari, Eudia Christina; Wahyono, Ari; Muryanto, Sigit; Mukti, Indro Kartiko; Amelia, Amelia (Jurnal Abdi Insani, 2024)
KWT Azalea Farm has the potential or assets that can be used as a place for edu-agrotourism. However, there are still many weaknesses or deficiencies that must be fixed in order to become a mini edu-agrotourism that is worth visiting. The purpose of this activity is to improve the economy of the surrounding community through more competitive edu-agrotourism management so that it is expected that there will be an increase in income and the creation of food security. The method chosen to solve the problem is the ABCD (Asset Based Community Development) approach as well as counseling, training and mentoring. The results of the activity are an increase in the understanding and knowledge of partners related to managing edu-agrotourism, managing websites and the ability to process animal waste into fertilizer. The conclusion of this activity is that partners receive benefits from the activities that have been carried out, and begin to improve to make KWT Azalea Farm a mini edu-agrotourism that is worth visiting. Product marketing begins to utilize website media by managing the website more seriously. Sheep waste has been processed into fertilizer using a flouring machine and has been successfully sold, increasing income. The hope for the future is that the potential that KWT Azalea Farm currently has can be maintained and managed well so that it can continue to provide benefits to the surrounding community.